2021
DOI: 10.3389/fmicb.2021.687103
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Survey of Bacterial Species in the Guts of Black Soldier Fly Larvae (Hermetia illucens) Reared on Two Urban Organic Waste Streams in Kenya

Abstract: Globally, the expansion of livestock and fisheries production is severely constrained due to the increasing costs and ecological footprint of feed constituents. The utilization of black soldier fly (BSF) as an alternative protein ingredient to fishmeal and soybean in animal feed has been widely documented. The black soldier fly larvae (BSFL) used are known to voraciously feed and grow in contaminated organic wastes. Thus, several concerns about their safety for inclusion into animal feed remain largely unaddre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…To elaborate on these findings, this work also looked at additional substrates to test that assumption and included, for the first time, the analysis of the microbial community in the hindgut. In fact, to the best of our knowledge, the microbial composition of BSF larval gut was analyzed either on the whole organ (Klammsteiner et al, 2020;Shumo et al, 2021;Zhang et al, 2021;IJdema et al, 2022) or by subdividing the midgut in its three main regions (Bruno et al, 2019b). The introduction of the hindgut as separate sample provides new, interesting insights.…”
Section: Bacterial Community Dynamics Throughout the Bsf Larval Gut R...mentioning
confidence: 99%
“…To elaborate on these findings, this work also looked at additional substrates to test that assumption and included, for the first time, the analysis of the microbial community in the hindgut. In fact, to the best of our knowledge, the microbial composition of BSF larval gut was analyzed either on the whole organ (Klammsteiner et al, 2020;Shumo et al, 2021;Zhang et al, 2021;IJdema et al, 2022) or by subdividing the midgut in its three main regions (Bruno et al, 2019b). The introduction of the hindgut as separate sample provides new, interesting insights.…”
Section: Bacterial Community Dynamics Throughout the Bsf Larval Gut R...mentioning
confidence: 99%
“…and Bordetella sp. were detected in KW [29]. When screened and isolated bacteria from the gut of Black Soldier larvae treated rice straw feed, Supriyatna, and Ukit (2016) [30] found that six out of nine cellulose degrading bacteria belonged to Bacillus, where Bacillus sp.…”
Section: Identification Results Of Selected Bacteriamentioning
confidence: 99%
“…According to a previous study, Morganella morganii and Providencia spp. together have the ability to produce urease, which results in the generation of significant amounts of biogenic amines, which could neutralize the gut’s acidic digestive fluids, preventing some bacterial species from being hydrolyzed [ 37 ]. Thus, the decline of Morganella and Providencia in GT1–2 and PT1–2 might have an impact on larval digestion and the gut microbial composition.…”
Section: Discussionmentioning
confidence: 99%